A CFD Investigation of Sailing Yacht Transom Sterns - Allroth, Jens; Wu, Ting-Hua (My University, 2014)
The objective of this thesis was to investigate whether the hydrodynamic performance of the wide, box-shaped transoms that have become very popular on modern performance cruisers is better than the performance of the more conventional, less wide, rounder transoms. The investigation of the hydrodynamic performance was evaluated with the aid of computational fluid dynamics using the Reynolds Average Navier-Stokes (RANS) viscous solver SHIPFLOW 5.0 with Volume of Fluids method surface capturing (VOF). First part of the study was to conduct verification of the software using the Least Square Root method. Second part was to make a validation of the software where Computational Fluid Dynamics (CFD) results were compared to experimental data from towing tank tests of Delft Systematic Yacht Hull Series (DSYHS) hulls. In the third part an average modern performance cruiser was designed to later be used as a base line for a systematic transom geometry variation study. Twelve hulls were created with varying transom size and shape. Each hull was tested in four conditions; upright and heeled condition at Froude numbers 0.35 and 0.60. Finally the results from the CFD computations were used to set up a simple upwind-downwind race to distinguish which hull that had the best overall performance. In the upwind-downwind race the round transoms performed best for the three fastest transom sizes. The fastest hull around the course has an immersed transom ratio (At/Ax) of 0.16 and it is 1.9 % faster with round transom than with boxy. The study has led to better understanding of the relation between hydrostatic and hydrodynamic resistance at high Froude numbers where the gain from a big immersed transom area is larger than the loss from increased transom resistance. Also, the influence on wave resistance from the curvature of the water and buttock lines has been clearly illustrated. For low Froude numbers, where the transom is wetted, the effect from viscous pressure resistance, base drag, has been pinpointed.
Keywords: Farkostteknik; Vehicle Engineering